My kind of place : travel stories from a woman who's been everywhere - Orlean, Susan (Random House Trade Paperbacks, 2005)
"In My Kind of Place, Susan Orlean takes readers on a series of remarkable journeys in a uniquely witty and sophisticated travel book. In this collection of adventures far and near, Orlean conducts a tour of the world via its subcultures, from the heart of the African music scene in Paris to the World Taxidermy Championships in Springfield, Illinois - and even into her own apartment, where she imagines a very famous houseguest taking advantage of her hospitality."--Jacket.